2017
DOI: 10.1371/journal.pone.0186370
|View full text |Cite
|
Sign up to set email alerts
|

Actinide bioimaging in tissues: Comparison of emulsion and solid track autoradiography techniques with the iQID camera

Abstract: This work presents a comparison of three autoradiography techniques for imaging biological samples contaminated with actinides: emulsion-based, plastic-based autoradiography and a quantitative digital technique, the iQID camera, based on the numerical analysis of light from a scintillator screen. In radiation toxicology it has been important to develop means of imaging actinide distribution in tissues as these radionuclides may be heterogeneously distributed within and between tissues after internal contaminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It is important therefore to consider this when tissues are analysed many years after the actual contamination. More recent experiments using the iQID (ionizing-radiation Quantum Imaging Detector) camera where activity can be measured directly on a tissue section results showed that in lungs from MOX-contaminated rats, higher levels of activity were found in areas of fibrosis as compared with non-fibrotic regions 2 . This technique however has the advantage of being non-destructive and measures activity directly as opposed to dissection and lengthy destructive radiochemical procedures.…”
Section: Exploitation Of Samples From the Repository: Examplesmentioning
confidence: 99%
“…It is important therefore to consider this when tissues are analysed many years after the actual contamination. More recent experiments using the iQID (ionizing-radiation Quantum Imaging Detector) camera where activity can be measured directly on a tissue section results showed that in lungs from MOX-contaminated rats, higher levels of activity were found in areas of fibrosis as compared with non-fibrotic regions 2 . This technique however has the advantage of being non-destructive and measures activity directly as opposed to dissection and lengthy destructive radiochemical procedures.…”
Section: Exploitation Of Samples From the Repository: Examplesmentioning
confidence: 99%
“…Due to their versatility and high sensitivity, polymeric NTDs have been extensively used to generate autoradiographies of biological samples for different applications. For example, they have been applied to perform actinide bioimaging in tissues [18] and to determine uranium distribution in rat kidney sections [19]. In the context of BNCT, the autoradiographic image of a histological section coming from a boron-loaded sample is obtained by irradiating the sample-detector assembly with thermal neutrons and later etching to enlarge the particle damage.…”
Section: Introductionmentioning
confidence: 99%
“…The question of the fate of tissue-retained actinides, even initially soluble ones, has been studied particularly with regard to deposition and retention in lungs and eventual effective dose ( International Commission on Radiological Protection(ICRP), 1994a ). Retention compartments in the lungs can be macrophages, interstitial connective tissue as well as scar tissue ( Hahn et al, 2004 ; Van der Meeren et al, 2012 ; Van der Meeren et al, 2014 ; Lamart et al, 2017 ; Birchall et al, 2019 ). Regardless of contaminant solubility (from soluble to insoluble forms such as oxides and metals), retained activity may be considered as a “reservoir”.…”
Section: Introductionmentioning
confidence: 99%